Cross-sectional survey of COVID-19-related impacts on mental health of nurses: occupational disruption, organisational preparedness, psychological harm, and moral distress. Issue 2 (4th May 2022) - Pascoe, Amy; Paul, Eldho; Willis, Karen; Smallwood, Natasha
Abstract : Background : The COVID-19 pandemic has presented unprecedented levels of prolonged strain on healthcare systems and healthcare workers (HCWs) globally, with nurses at the forefront. Objectives : To describe types and prevalence of occupational disruptions and exposure to COVID-19, and their impacts on mental health, moral distress, coping strategies, and help-seeking behaviours of Australian nurses. Design : A cross-sectional online anonymous survey distributed amongst Australian HCWs between 27 August and 23 October 2020. Methods : Data was collected on demographics, workplace disruption, personal relationships, and mental health. Predictors of mental health impacts and coping strategies were identified through multivariate regression analyses. Results : 7845 complete responses were returned, of which 3082 (39.3%) were from nurses and 4763 (60.7%) were from all other professions ('other HCWs'). Occupational disruption was common, with nurses specifically reporting additional paid hours ( p < 0.001). Nurses were exposed to, and infected with, COVID-19 more frequently than other HCWs ( p < 0.001) and were more likely to report concerns around stigmatisation from the broader community ( p < 0.001). Symptoms of mental illness (anxiety, depression, PTSD and burnout) were significantly more prevalent in nurses than other HCWs, despite both groups scoring high on resilience. Common predictors of mental health symptoms included exposure to COVID-19 and worsening of personal relationships. Nurses reported a variety of coping strategies and were more likely than other HCWs to increase alcohol consumption. Engagement with formal support services was low for both groups. Personal and professional predictors for coping strategy use were identified. Conclusions : Urgent action is needed to address staff shortages and burnout which have been exacerbated by COVID-19. Initiatives that recognise the importance of nursing staff and incentivise current and future nurses to join and remain in the workforce are essential.